Phytochemical study of Gypsophila trichotoma wend. (Caryophyllaceae) - Ilina N. Krasteva; Ivo S. Popov; Vessela I. Balabanova; Stefan D. Nikolov; Ivanka P. Pencheva (Química Nova, 2008)
Phytochemical studies of ethyl acetate extracts from the roots and aerial parts of Gypsophila trichotoma revealed the presence of stigmast-7-en-3-ol, stigmasta-7,22-dien-3-ol (spinasterol), ergost-7-en-3-ol, stigmasta-3,5dien7-one, β-sitosterol, 22,23-dihydrospinasterone, vitexin, orientin, homoorientin and hyperoside. The structures of the compounds were determined by GC/MS and HPLC analyses.